PENGARUH KEBIJAKAN DIVIDEN, STRUKTUR ASET, PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - admin, RAFIQAH HAYATI B11112014 (Jurnal Manajemen Update, 2017)
This research aims to examine and analyze the effect of dividend policy, asset structure,profitability and firm growth toward leverage policy on manufacturing companies listed in IndonesiaStock Exchange for 2010-2014 period. Independent variables in this research are Dividend Policy,Asset Structure, Profitability and Firm Growth. Dependent variable in this research is Leverage Policy.The type of this research is quantitative research. The research population covers allmanufacturing companies listed on the Indonesia Stock Exchange. The sample was collacted bypurposive sampling method. The data of this research population as many as 147 companies, andobtained a sample of 16 companies. The analysis technique used by this research is multiple linearregression, used SPSS 16.0 program with simultaneous test (Test F), and partial test (t test).The result of this research showed that Dividend Policy had a significant influence withnegative coefficient on Leverage Policy. Asset Structure had a significant influence with positifcoefficient on Leverage Policy. Profitability had a significant influence with negative coefficient onLeverage Policy. And firm growth had no significant influence on Leverage Policy. Simultaneous testof dependent variables had a significant influence to Leverage Policy. The ability of dependent variablescan explain the effect to Leverage policy by 16% as shown by amount of adjusted R square by 16%,while the remaining 84% was influenced by other factors beyond this research.Keyword : Dividend Policy, Asset Structure, Profitability, Firm Growth, Leverage Policy